2017
DOI: 10.1080/01902148.2017.1354408
|View full text |Cite
|
Sign up to set email alerts
|

The activity of nintedanib in an animal model of allogenic left lung transplantation resembling aspects of allograft rejection

Abstract: In conclusion, while nintedanib reduced the expression of growth factors/receptors in a rat LTx model, a reduction in fibrotic alterations was not observed at POD 60.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…In a rat model of left-lung allotransplantation, no reduction in fibrotic changes was observed in nintedanib-treated allografts compared to non-treated allografts, despite reduced expression of growth factors. Early and sustained treatment did not decrease the number of rats with histological signs of acute or chronic rejection [57].…”
Section: Mechanisms Of Antifibrotics On the Pathophysiological Processes After Ltx And In Clad Developmentmentioning
confidence: 79%
See 1 more Smart Citation
“…In a rat model of left-lung allotransplantation, no reduction in fibrotic changes was observed in nintedanib-treated allografts compared to non-treated allografts, despite reduced expression of growth factors. Early and sustained treatment did not decrease the number of rats with histological signs of acute or chronic rejection [57].…”
Section: Mechanisms Of Antifibrotics On the Pathophysiological Processes After Ltx And In Clad Developmentmentioning
confidence: 79%
“…Adequate treatment of CLAD remains a significant unmet need. Based on the mechanisms of action, there is a particular interest in the use of antifibrotics in these patients, as pirfenidone and nintedanib could reduce development of obliterative and constrictive bronchiolitis, the histological correlate of BOS, and parenchymal and interstitial fibrosis, the histological correlate of RAS [57].…”
Section: Mechanisms Of Antifibrotics On the Pathophysiological Processes After Ltx And In Clad Developmentmentioning
confidence: 99%
“…This is particularly relevant when considering that at this stage of the disease, the level of lung function is likely to be low and that the evidence from the clinical trials and the real-world data suggests that these patients are more likely to make it to the transplant if they are on anti-fibrotic treatment. A pre-clinical lung transplantation study in rats revealed no evidence of impaired wound healing despite nintedanib being administered before and after the surgical procedure [44] and a small case study in Belgium (nintedanib, n = 2) showed no problems with bleeding or delayed wound healing related to anti-fibrotic treatment. There were some mild complications with anastomosis between the transplanted organ and the trachea in some patients; however, these were mild or uneventful [45].…”
Section: Expert Statements and Recommendationsmentioning
confidence: 99%
“…On the other hand, downregulation of both PDGFR subtypes in our experimental model might be the mechanistic link between nintedanib treatment and inhibition of SMC proliferation. Suesskind-Schwendi et al 44 used nintedanib in a rat lung transplantation model and also found receptor down-regulation (PDGFRα and VEGFR2), but interestingly did not reveal decreased fibrosis development after lung transplantation. This controversy to our results can be explained by a different pathomechanism in the aortic transplant model: neointima formation in CAV initially is driven by SMC proliferation and accumulation as well as leukocyte infiltration whereas fibrosis represents only a minor aspect in CAV.…”
Section: Discussionmentioning
confidence: 98%